Improving machining performance using alumina powder-added dielectric during electrical discharge machining (EDM) - Khan, Ahsan Ali; Abu Bakar, Marina; Al Hazza, Muataz Hazza Faizi; Che Daud, Mohd Radzi; Mohiuddin, A. K. M. (IOP Publishing, 2017)
Alumina powder was added to dielectric fluid during Electrical discharge machining (EDM) of AISI 304 steel. The main machining parameters of current (A), tool diameter (mm) and powder concentration (g/L) were chosen to determine the EDM machining characteristics of material removal rate (MRR), tool wear rate (TWR) and surface roughness (Ra). This work adopted two-level full factorial experiments. The significant factors that affect the MRR and tool TWR are current, tool diameter and powder concentration. The MRR increases when the current and tool diameter are higher. The presence of powder concentration also increases the MRR. The higher current used and the presence of powder concentration increase the TWR. Meanwhile, a smaller tool diameter gives higher value of TWR. Current and powder concentration are the significant factors to determine the surface roughness of work surfaces. Higher current applied gives high surface roughness, but higher powder concentration gives improved surface finish.